Cooperative surveillance systems and digital-technology enabler for a real-time standard terminal arrival schedule displacement. (October 2021) - Xue, Dabin; Hsu, Li-Ta; Wu, Cheng-Lung; Lee, Ching-Hung; Ng, Kam K.H.
Abstract: As the backbone of Communications, Navigation and Surveillance Systems for Air Traffic Management (CNS/ATM), Automatic Dependent Surveillance-Broadcast (ADS-B) is a surveillance technology and digital-technology enabler relying on the Global Navigation Satellite System (GNSS). The onboard ADS-B Out system broadcasts the aircraft's real-time digital information such as position and ground speed periodically (every 0.5–2 s), which is more frequent than the radar system. Taking this advantage, situational awareness and flight efficiency can be highly improved. In this paper, a novel heuristic search method based on ADS-B is proposed for the Aircraft Landing Problem (ALP) with the objective of reducing flight time while maintaining the time separation standards mandated by the International Civil Aviation Organization (ICAO). The recorded ADS-B data in Shanghai Hongqiao and Pudong international airports are adopted to demonstrate the performance of the proposed method. Results show that there is an obvious decrease in the total flight time. Besides, the heuristic search method can achieve continuous and real-time ALP updates, satisfying the requirements for air traffic control. While highlighting ADS-B-based applications, this study also provides some basic implications for the updated model in air traffic management.